Influências de instituições externas à escola pública: privatização do ensino a partir da educação ambiental? - Mendes, Carolina Borghi [UNESP] (2015)
From observing the diversity of actions charged with different ideologies that have been developed as environmental education (Educação Ambiental - EA) at school environment, which includes actions offered by institutions outside the educational context, belonging to the private sectors of great economic relevance in Brazil, emerged the need too evaluate the goals and consequences of such, under the optical of the transformation - or maintenance - of the current corporate model. Thus, our investigative and analytical goal in this dissertation was to get to know is the insertion, in public shools from the cities of Dumont, Pradópolis, Jaboticabal e Rincão, of the Associação Brasileira do Agronegócio - ABAG (Brazilian Association of Agribusiness), through its program Agronegócio na Escola (Agribusiness at school) and the partnership o a sugarcane factory with the association, who offers visits to its Center of Environmental Education (Centro de Educação Ambiental - CEA), to the students. To collect information, we made visits, to the CEA, conducted surveys and interviewed teachers, municipal secretaries and/or representatives of the City Boards of Education (Secretarias Municipais de Educação - SMEs) of said cities, as well as a representative of ABAG of Ribeirão Preto, aiming to comprehend how the actions that have been developed in partnership between those two institutions interfere in the work of teachers and public education, specially EA and its insertion - under a given perspective - in the shool context. We adeopted as a theoretical-methodological reference the Materialism Historical-Dialectical, supported, still, by the triangulation and categorization of the data obtained to present more clearly our analysis. We found that the insertion of outside institutions - of such economic and cultural relevance in the area sampled - in the public schools, interferes in the work of teachers and in the development of a...